A Case Report on Purple Urine Bag Syndrome - Nedamanuru, Kavya; Dampetla, Sai Jyothi; Gopineni, Divya (Indian Journal of Pharmacy Practice)
Discoloration of urine is not uncommonly encountered in clinical practice and may indicate a significant pathology. However, the majority of instances are benign and occur as the result of trauma to the urological system during procedures or ingestions of substances such as medication or food. This phenomenon is known as the purple urine bag syndrome. It is associated with urinary tract infections occurring in catheterised patients, generally elderly females with significant co-morbidities and constipation. The purple discoloration is most often due to the presence of indigo and indirubin pigments which are the metabolites of tryptophan. In this article, we present a case of elderly man with this rare and interesting phenomenon after insertion of an indwelling catheter. The purple urine disappeared after antibiotic therapy.
Keywords: Purple urine bag syndrome; Tryptophan; Catheterisation; Antibiotic therapy